2021
DOI: 10.1155/2021/2048833
|View full text |Cite
|
Sign up to set email alerts
|

Genome Instability-Related miRNAs Predict Survival, Immune Landscape, and Immunotherapy Responses in Gastric Cancer

Abstract: Background. Increasing evidence suggests that microRNAs (miRNAs) are involved in genome instability (GI) and drive the occurrence of tumors. However, the role of GI-related miRNAs in gastric cancer (GC) remains largely unknown. Herein, we developed a novel GI-related miRNA signature (GIMiSig) and further investigated its role in prognosis, the immune landscape, and immunotherapy responses in GC patients. Methods. An analysis of somatic mutation data on 434 gastric cancer cases from The Cancer Genome Atlas (TCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Mutations in TTN , the gene encoding giant myofilament titin, cause familial dilated cardiomyopathy ( 45 ). Study has shown that patients with a high frequency of TTN mutations have a better prognosis, which is similar to our results ( 46 ). Yang et al found that TTN mutations were effective in predicting GC prognosis, tumor mutation burden (TMB), and immunotherapy response ( 47 ).…”
Section: Discussionsupporting
confidence: 93%
“…Mutations in TTN , the gene encoding giant myofilament titin, cause familial dilated cardiomyopathy ( 45 ). Study has shown that patients with a high frequency of TTN mutations have a better prognosis, which is similar to our results ( 46 ). Yang et al found that TTN mutations were effective in predicting GC prognosis, tumor mutation burden (TMB), and immunotherapy response ( 47 ).…”
Section: Discussionsupporting
confidence: 93%
“…We used the "Gene" module of SangerBox (6), a web-based program (http://www.sangerbox.com), to examine the mRNA expression levels of PLK4 in different tumor and normal tissues as reported by TCGA and performed an integrated analysis of the TCGA (7) and GTEx (8) databases. Furthermore, several TCGA tumors were analyzed using the "Pathological Stage Plot" module of GEPIA2.…”
Section: Materials and Methods Mrna Expression Analysismentioning
confidence: 99%
“…Similarly, Liu et al also constructed the GI-related miRNAs signature (GIMiSig) for predicting the survival rate of GC patients based on eight miRNAs, and compared it with the current clinically commonly used cancer staging methods. As a result, GIMiSig achieved a better prediction effect on the survival rate of GC patients [ 86 ]. In addition, Qi et al built a risk scoring formula based on three miRNAs including miRNA-126-3p, miRNA-143-5p, and miRNA-1275, which was verified and might be used to predict the prognosis of GC patients [ 87 ].…”
Section: Mirnas and Cancer Diagnosis And Prognosismentioning
confidence: 99%